Design, synthesis and biological evaluation of novel piperic acid and benzylpiperazine hybrid molecules for improvement of memory impairment via cholinesterase inhibitory activity - Kumar J.; Shankar G.; Kumar S.; Singh G.; Gajendra T.A.; Rai S.; Mandloi U.; Srikrishna S.; Kumar S.; Singh A.K.; Kumar P.; Tiwari K.N.; Krishnamurthy S.; Modi G.; Mishra S.K. (My University, 2025)
In this paper, we have developed a series of piperic acid (PA) derivatives to overcome the inherent constraints linked to PA for Alzheimer's disease (AD) management. We have carried out a comprehensive study to investigate the structure–activity relationship (SAR) of PAanalogs to enhance their inhibitory properties towards cholinesterase enzymes. Compound 3m exhibited notable inhibition against butyrylcholinesterase (BChE) and acetylcholinesterase (AChE) among all developed analogs (BChE (µM), 1.03 ± 0.011; AChE (µM), 4.26 ± 0.13 respectively) over PA (AChE% inhibition at 20 µM, 7.14 ± 0.98; BChE% inhibition at 20 µM, 5.87 ± 0.76). Compound 3m was chosen for further biological investigations based on these encouraging outcomes. 3 m demonstrated a binding affinity for AChE’s peripheral anionic site, indicating its interaction with this specific enzyme region. Additionally, it also possesses favorable permeability across the blood–brain barrier, with a Pe (permeability coefficient) value of 5.79 ± 1.12. The molecular docking investigations unveiled the ability of 3mto intricately engage with AChE and BChE.In cell-based cytotoxicity tests, compound 3m displayed cell-friendly characteristics across different tested concentrations. Notably, 3m exhibited the ability to counteract scopolamine-induced memory impairmentin mice, enhancing both spatial and cognitive memories. These results strongly suggest that 3m can behave as a potential compound for AD management. © The Author(s), under exclusive licence to the Institute of Chemistry, Slovak Academy of Sciences 2024.